2021
DOI: 10.1038/s41419-021-04356-6
|View full text |Cite
|
Sign up to set email alerts
|

USP5 facilitates non-small cell lung cancer progression through stabilization of PD-L1

Abstract: PD-L1(CD274) is a well-known immunosuppressive molecule, which confers immunoescape features to cancer cells and has become one of the major targets in cancer immunotherapies. Understanding the regulatory mechanisms that control PD-L1 protein expression is important for guiding immune checkpoint blockade therapy. Here, we showed that ubiquitin specific peptidase 5 (USP5) was a novel PD-L1 deubiquitinase in non-small cell lung cancer (NSCLC) cells. USP5 directly interacted with PD-L1 and deubiquitinated PD-L1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Abundant evidence indicates that USP5 expression is elevated in NSCLC cancers 13 , 17 19 , while the correlation of Beclin 1 protein expression with NSCLC remains debatable 37 . We thus examined the expression of USP5 and Beclin 1 in human lung adenocarcinoma biopsy samples and paired adjacent tissue via IHC, followed by analyses of Average Optical Density (AOD) 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Abundant evidence indicates that USP5 expression is elevated in NSCLC cancers 13 , 17 19 , while the correlation of Beclin 1 protein expression with NSCLC remains debatable 37 . We thus examined the expression of USP5 and Beclin 1 in human lung adenocarcinoma biopsy samples and paired adjacent tissue via IHC, followed by analyses of Average Optical Density (AOD) 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitination assay was carried out following a previously published method [ 28 ]. Briefly, the cells were resuspended in the lysis buffer containing protease inhibitor and subjected to ultrasonic lysing.…”
Section: Methodsmentioning
confidence: 99%
“…Programmed death ligand-1 (PD-L1) is a crucial immune checkpoint molecule and downregulates T-cell immune responses by binding to programmed death protein-1 (PD-1). Emerging evidence indicates that the protein stabilization of PD-L1 is regulated by several DUBs, such as USP5, USP22, and USP9X ( Hu et al, 2021 ; Pan et al, 2021 ). Notably, a recent study found that USP21 could also deubiquitylate and stabilize PD-L1, suggesting a potential role of USP21 in immunosuppression ( Yang et al, 2021 ).…”
Section: Role Of Usp21 In Diverse Biological Processesmentioning
confidence: 99%